Sinergi Pemerintah dan Masyarakat dalam Pengelolaan Sampah di Pulau Dom Distrik Sorong Kepulauan - Saragih, Fauziah; Halik, Wahyudin; Ali, Muhammad; Salmawati, Salmawati; Refra, Mohamad Saleh; Fikri, Awal; Rais, Lukman; Ayswhara, Halizah; Yekwam, Markus; Making, Michelle (Abdimas: Papua Journal of Community Service, 2025)
This community service program was carried out to enhance knowledge, awareness, and community engagement in waste management on Dom Island, Sorong Islands District. The primary issue faced by the local community is a limited understanding of the negative impacts of waste and the lack of household waste sorting and recycling practices. To address these challenges, the implementation team employed a participatory approach through a socialization session held on June 16, 2025. The activity involved active participation from district government officials, community leaders, religious figures, and local residents. The materials presented included an introduction to types of waste, the dangers of pollution, and the implementation of the 3R principles (Reduce, Reuse, Recycle). The outcomes of the activity indicated an increased level of community understanding and commitment to environmental management, alongside the emergence of initiatives such as the formation of environmental volunteer groups and plans to establish a local waste bank. The synergy between government and community has proven to be a crucial factor in fostering collective behavioral change toward a cleaner and more sustainable environment